Fountain Holiday - Jonuzakov Abduvali Esirgapovich; Jonuzakova Gavkhar Abduvalievna (Researchparks Publishing, 2022)
The article is devoted to the importance of water and fountains in cities with hot-dry climates, their planning and organization, the use of modern technologies in their system.